Prophets of progress: How do leading global agencies naturalize enchanted determinism surrounding artificial intelligence for education? (Journal of Applied Learning and Teaching, 2025)
The hype surrounding AI for education continues with no sign of dying down in the near term. Given the influence of UNESCO and OECD on national educational policies worldwide, this study examined how they frame artificial intelligence (AI) and how their discourse may affect the wider educational landscape. Drawing upon the theory of Critical Discourse Analysis, this study adopted a two-stage analysis method: framework analysis followed by directed qualitative content analysis. Four themes were identified, including the necessity of AI-driven educational transformation, imagined educational futures enabled by AI, challenges brought about by AI for education, and solutions and walkthroughs. They were critiqued using the schema of practical argument proposed for political discourse analysis which is composed of a Value premise, a Goal premise, a Circumstantial premise, a Means–Goal premise and a Claim (or conclusion). Findings show that while admitting the existence of enormous uncertainties and challenges, UNESCO and OECD take for granted AI’s disruptiveness, inevitability, and potential to change education, its effect on the whole society for the better and its encouragement of the acceleration of AI for education. Possible ramifications of this framing on the ecology of education and beyond were then discussed. The article concludes by calling for a vigilant and critical approach to the AI narratives promoted by influential global agencies, arguing that the future of education depends on our ability to question, adapt and thoughtfully integrate technology without succumbing to unexamined inevitabilities or unwarranted optimism.